2002
DOI: 10.1002/mds.10132
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for shoulder girdle dystonia in selected patients with cervical disc prolapse

Abstract: Some patients with cervical disc herniation suffer from persistent nuchal pain and muscle spasms after decompressive surgery despite the lack of clinical and radiological signs for actual spinal root compression. Sonographic examination of the brain in some of these patients showed increased echogenicity of the lentiform nuclei as described in patients with idiopathic dystonia. This has been linked to an altered Menkes protein level and copper metabolism. We suggest a relationship between persistent nuchal pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…The same finding is frequently observed in patients with upper limb dystonia (83%), but less often in patients with facial dystonia (31%) and only rarely in healthy controls (12%) 116. Areas of hyperechogenicity in idiopathic dystonia are larger contralateral to the clinically affected side, and the intensity of hyperechogenicity seems to correlate with the severity of the dystonic symptoms 116. Interestingly, a strikingly high percentage of patients with herniated cervical discs and nuchal pain show hyperechogenicity of the LN 117.…”
Section: Transcranial Sonographysupporting
confidence: 73%
See 1 more Smart Citation
“…The same finding is frequently observed in patients with upper limb dystonia (83%), but less often in patients with facial dystonia (31%) and only rarely in healthy controls (12%) 116. Areas of hyperechogenicity in idiopathic dystonia are larger contralateral to the clinically affected side, and the intensity of hyperechogenicity seems to correlate with the severity of the dystonic symptoms 116. Interestingly, a strikingly high percentage of patients with herniated cervical discs and nuchal pain show hyperechogenicity of the LN 117.…”
Section: Transcranial Sonographysupporting
confidence: 73%
“…Increased echogenicity of the lentiform nucleus (LN) has been observed in up to 75% of patients with cervical dystonia 114, 115. The same finding is frequently observed in patients with upper limb dystonia (83%), but less often in patients with facial dystonia (31%) and only rarely in healthy controls (12%) 116. Areas of hyperechogenicity in idiopathic dystonia are larger contralateral to the clinically affected side, and the intensity of hyperechogenicity seems to correlate with the severity of the dystonic symptoms 116.…”
Section: Transcranial Sonographymentioning
confidence: 89%
“…Previous studies have repeatedly demonstrated disturbances of copper metabolism in primary dystonia by transcranial ultrasound [3,4,5], leukocyte analysis [6], and neurochemical analysis of trace metals and proteins in the brain tissue [7,8]. The findings were also reproduced in post-surgical secondary dystonia [9], implying the presence of subjects susceptible to dystonia, although the copper gene might be irrelevant by itself to the pathogenesis of dystonia [10]. …”
Section: Introductionsupporting
confidence: 49%
“…While standard structural magnetic resonance imaging (MRI) studies have not revealed any gross pathology in patients with primary dystonia, transcranial sonography (TCS) and voxel-based morphometry MRI detected changes in the globus pallidus of patients with primary spontaneous dystonia [4,5] . Increased echogenicity ('hyperechogenicity'), mainly in the medial part of the lenticular nucleus (LN), was detected on TCS in more than 75% of patients with spontaneous cervical or upper-limb dystonia [4,6] . To find out whether basal ganglia changes are also present in task-specific dystonia, we studied musicians with focal task-specific hand dystonia, unaffected musicians and unaffected nonmusicians with TCS.…”
Section: Introductionmentioning
confidence: 99%